2007
DOI: 10.1216/jiea/1192628618
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Estimate for the Norm of the Kerzman-Stein Operator

Abstract: Abstract. We establish an elementary lower estimate for the norm of the Kerzman-Stein operator for a smooth, bounded domain. The estimate involves the boundary length and logarithmic capacity. The estimate is tested on model domains for which the norm is known explicitly. It is shown that the estimate is sharp for an annulus and a strip, and is asymptotically sharp for an ellipse and a wedge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…An intimate relationship between Szegő projections and "Cauchy-like" integral operators C (the Leray transform is just one such example) was noticed by Kerzman and Stein in [24,25]. They observed that detailed information about the Szegő projection can be extracted from the operator A := C * − C. See [10] for an expository treatment of these ideas in the complex plane and [13,12,9,28] for more recent developments.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…An intimate relationship between Szegő projections and "Cauchy-like" integral operators C (the Leray transform is just one such example) was noticed by Kerzman and Stein in [24,25]. They observed that detailed information about the Szegő projection can be extracted from the operator A := C * − C. See [10] for an expository treatment of these ideas in the complex plane and [13,12,9,28] for more recent developments.…”
Section: Introductionmentioning
confidence: 93%
“…The operator A stems from work of Kerzman and Stein [24,25] examining the relation between certain particular Cauchy-Fantappiè projections and the self-adjoint Szegő projection S (corresponding to K = 0). See [13,12,5,16,10] for results on A in the one-dimensional setting and [9] for results on Reinhardt domains.…”
Section: Related Operatorsmentioning
confidence: 99%
“…Subsequent work on the problem was concerned with giving a complete description of the spectrum for model domains [3], asymptotics of eigenvalues for ellipses with small eccentricity [5], and norm estimates that are invariant with respect to Möbius transformation [1,4]. For a disc or halfplane, there is complete cancellation of singularities and the Kerzman-Stein operator is trivial [13].…”
Section: Theoremmentioning
confidence: 99%
“…(Recall that the essential norm -see [13] -measures the distance to the set of compact operators; it often occurs in localized analysis.) See [5,9,10] for related results about C.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can also be extracted from this work that the essential L 2 -norm C e = 1 for every smooth Ω ⊂ C. (Recall that the essential norm -see [13] -measures the distance to the set of compact operators; it often occurs in localized analysis.) See [5,9,10] for related results about C.…”
Section: Introductionmentioning
confidence: 99%